(untitled) (International journal of artificial intelligence, 2025)
This article explores the effectiveness of innovative technologies in enhancing lexical competence of EFL students. The study scrutinize numerous methods aimed to improving language learners’ vocabulary technology-oriented learning approaches like mobile applications, gamification and the integration of blended learning and online learning models. The investigation emphasize on how autonomous learning, personalized instruction and immediate feedback contribute to becoming the learning process more effective and practical. Moreover, this article focuses on the role of teachers and their pedagogical competences in this enriching learners’ lexical resource.